2021
DOI: 10.1021/acsami.1c07037
|View full text |Cite
|
Sign up to set email alerts
|

Self-Activating Therapeutic Nanoparticle: A Targeted Tumor Therapy Using Reactive Oxygen Species Self-Generation and Switch-on Drug Release

Abstract: One of the recent advances in nanotechnology within the medical field is the development of a nanoformulation of anticancer drugs or photosensitizers. Cancer cell-specific drug delivery and upregulation of the endogenous level of reactive oxygen species (ROS) are important in precision anticancer treatment. Within our article, we report a new therapeutic nanoformulation of cancer cell targeting using endogenous ROS self-generation without an external initiator and a switch-on drug release (ROS-induced cascade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…These results showed that the nanocarrier can stabilize a photolytically unstable ICG and significantly enhance the photodynamic performance (Figure f). , In the release profile analysis of ICG within SIWV-pSiNP­(ICG), 808 nm laser treatment accelerated the release of the incorporated ICG due to ROS generated from ICG, with laser-induced quickened degradation of pSiNPs (Figure g). The produced ROS from ICG accelerated the degradation rate of porous silicon nanoparticles, and the mechanism is that ROS oxidized silicon to silanol (S–OH) formation on the surface of nanoparticles and converted it to the soluble formation (orthosilicic acid, (Si­(OH) 4 )). ,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results showed that the nanocarrier can stabilize a photolytically unstable ICG and significantly enhance the photodynamic performance (Figure f). , In the release profile analysis of ICG within SIWV-pSiNP­(ICG), 808 nm laser treatment accelerated the release of the incorporated ICG due to ROS generated from ICG, with laser-induced quickened degradation of pSiNPs (Figure g). The produced ROS from ICG accelerated the degradation rate of porous silicon nanoparticles, and the mechanism is that ROS oxidized silicon to silanol (S–OH) formation on the surface of nanoparticles and converted it to the soluble formation (orthosilicic acid, (Si­(OH) 4 )). ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…The loading efficiency of ICG was calculated using the following eq 1 (see the Experimental section). 46 The concentration of the unloaded ICG was determined from the standard absorption curve of ICG (Figure S4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations